Factors Affecting Firm Performance: Does Corporate Governance Implementation Matter? - Yuli Soesetio; Dyah Arini Rudiningtyas; Aulia Claraning Sukmawati (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – This study aims to investigate the impact of corporate governance implementation on the dynamics of firm performance in the non-financial sector firms listed on the Indonesia Stock Exchange (IDX). Methodology/approach – This study uses secondary data from the financial statements of non-financial sector firms, between 2010 and 2018. The number of samples that met the established criteria was 88 firms, which were further analyzed using panel regression analysis common effect model. Findings – This study concludes that the implementation of corporate governance (board meeting and board size) in the non-financial sector, has a positive impact on firm performance. Low frequency of board meetings will worsen firm performance, whereas a high frequency of board meetings can improve company performance. In addition, financial information (i.e., leverage, sales growth, and asset turnover), and firm size has a significant impact on firm performance. Novelty/value – This study contributes to providing more general and robust conclusion regarding the effect of implementing corporate governance mechanisms on firm performance listed on IDX, especially in non-financial sector.